Distribution of points on spherical objects and applications - Selvitella, Alessandro; Selvitella, Alessandro (My University, 2013)
In this thesis, we discuss some results on the distribution of points on the sphere, asymptotically when both the number of points and the dimension of the sphere tend to infinity. We then give some applications of these results to some statistical problems and especially to hypothesis testing.
Keywords: Probability; Statistics; Geometry; Hypothesis Testing; Analysis; Geometry and Topology; Multivariate Analysis; Other Statistics and Probability; Statistical Theory; Analysis